Quality of Life during Treatment with Lenvatinib for Thyroid Cancer: The Patients' Perspective beyond the Medical Evaluation. Issue 1 (13th March 2021) - Nervo, Alice; Ragni, Alberto; Piovesan, Alessandro; Marica, Valentina; Migliore, Enrica; Gallo, Marco; Arvat, Emanuela
Abstract : Background: Lenvatinib (LEN) has shown great efficacy but important toxicity in patients with advanced radioactive iodine-refractory (RAI-R) thyroid cancer (TC); a focused evaluation of its impact on patients' quality of life (QoL) is still lacking. Our prospective study investigated the impact of this drug on QoL in a group of RAI-R TC patients treated at our centre. Methods: All patients filled in two questionnaires before and during treatment: (1) the Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events adapted questionnaire, assessing prevalence, severity, and/or interference on daily activities of the most frequent symptomatic adverse events (AEs) reported in previous clinical trials during therapy with LEN, and (2) the European Quality of Life 5 Dimensions 3 Levels (EQ-5D-3L) questionnaire, providing the EQ-5D index and the EQ visual analogue scale (EQ-VAS). Data from baseline questionnaires were compared with those obtained 3, 6, and 12 months after the start of treatment. Results: In our population ( n = 20), an overall increased perception of symptomatic AEs emerged during treatment (statistically significant for abdominal pain, asthenia/fatigue, decreased appetite, and xerostomia). The median EQ-5D index and EQ-VAS scores after 3 months of treatment were lower than at baseline, almost returning to initial values after 12 months. Conclusion: RAI-R TC patients reported a general increase in prevalence and interference on daily activities of symptomatic AEs during therapy with LEN. Self-perceived QoL initially decreased during therapy. However, our data suggest that QoL could be restored after 12 months; this trend might partly reflect the impact of therapy optimisation.